Faktor-Faktor yang Berhubungan dengan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Rambah Hilir I Kabupaten Rokan Hulu Tahun 201 - Herlina Susmaneli (STIKes Hang Tuah Pekanbaru, 2013)
National target for practice exclusive breastfeeding is 80 %. Riau Provincial health Department in 2010 reported that the scope of exclusive breastfeeding at 25.40%. Report Rokan Hulu District Health Office, Rambah Hilir I public health center was one of four health centers that target attainment is still low at 26.5%. This study aims to determine the relationship of maternal knowledge, maternal employment, information from health and family support to exclusivfeeding. The results obtained frequency of exclusive breastfeeding in the Rambah Hilir I public health center 35.8%, p value of knowledge capital variable maternal work, information from health and family support are 0.001, 0.590, 0.006 and 0.029. In conclusion, the frequency of exclusive breastfeeding in the Work Area Rambah Hilir I public health center at 35.8% in 2012, the variables associated with exclusive breastfeeding is the variable of maternal knowledge, information from health and family support, and variables that are not related to the variable job mother.